The new Oxford book of war poetry - Stallworthy, Jon ([Oxford books of prose & verse], 2015)
"Jon Stallworthy's classic and celebrated anthology spans centuries of human experience of war, from Homer's Iliad, through the First and Second World Wars, the Vietnam War, and the wars fought since. This new edition, published to mark the centenary of the outbreak of the First World War, includes a new introduction and additional poems from David Harsent and Peter Wyton, among others. The new selection provides improved coverage of the two World Wars and the Vietnam War, and new coverage of the wars of the late twentieth and early twenty-first centuries."--Publisher's website.